POST COVID POLYOSTOTIC АVАSСULАR NЕСRОSIS: САSЕ RЕРОRTS - Bakhrom Mardonov; Abdulaziz Akhmedov; An Arslan Kuvandikovich; Asilova S. U. (Modern American Journals, 2025)
Avascular necrosis (AVN) is an infrequent but potentially debilitating condition that has been associated with corticosteroid therapy and, more recently, with SARS-CoV-2 (COVID-19) infection. This case report presents two instances of AVN occurring following COVID-19 illness and corticosteroid administration.In Case 1, a 68-year-old female developed AVN of the left femoral head approximately eight months after receiving dexamethasone as part of her COVID-19 treatment regimen. She subsequently underwent core decompression and total hip arthroplasty. Notably, AVN lesions were also identified in her right knee and shoulder joints.In Case 2, a 26-year-old male manifested bilateral AVN of the hips 24 months post-COVID-19 infection and corticosteroid therapy. He received core decompression surgery for both hip joints and later presented with AVN in both shoulder joints.